Spatial forecasting of red palm mite in Brazil under current and future climate change scenarios - Navia, Denise (2016)
The objective of this work was to predict the spatial distribution of the red palm mite, Raoiella indica (Acari: Tenuipalpidae), in Brazil under current and future climate change scenarios. A mapping method of species distribution based on the geographic information system (GIS) was used. The maps were constructed taking into account ranges of favorability for temperature and relative humidity. Favorability levels were defined considering the available information on pest biology and population dynamics. To characterize the current climatic conditions, information was referenced to the climate normal from 1961 to 1990. Future scenarios for the models were the A2 and B1 gas emission scenarios from the Intergovernmental Panel on Climate Change, focusing on the periods of 2011–2040, 2041–2070, and 2071–2100. The constructed maps showed that, for the reference period, Brazil presents extensive areas with favorable or very favorable conditions for the establishment of red palm mite populations. An increasing favorability was observed for future scenarios when compared with the reference period, indicating that the pest impact will worsen if it is already widely spread and causing damage in the country. Under current and future climate scenarios, most of the favorable and very favorable areas for red palm mite are in northeastern Brazil.